The nature of early Greek coinage – the case of Sicily - Rutter, Keith (Journal of Greek Archaeology, 2016)
Coins were made and circulated in their millions in the ancient world. By common consent they are part of the evidence for the reconstruction of ancient history of all kinds, economic, artistic, religious, political. But how can the evidence provided by coins best be exploited? In a recent article, I suggested that it is on the basis of ‘detailed work on the numismatic material, on the structure and volume of different coinages, on the ‘rhythms’ and rates of production, that we can expect worthwhile contributions to debates about the impact (revolutionary?) of coinage in the Greek world, the speed and degree to which parts of it were monetized (rapid and total?), and the organized development of a market economy (buying and selling in the agora?).’ In the present paper I take up that challenge by examining in detail the earliest coinage in one part of the Greek world, the island of Sicily. What can it tell us about the nature and impact of early Greek coinage?